Trophic morphology and diet of the endangered fish Tlaloc hildebrandi (Cyprinodontiformes: Profundulidae). - Domínguez-Cisneros, Sara Elizabeth; Kobelkowsky, Abraham; Velázquez-Velázquez, Ernesto (Revista de Biología Tropical, 2023)
Introduction: Tlaloc hildebrandi is a freshwater killifish, endemic to southern Mexico and under threat of extinction; the knowledge of the trophic morphology and diet is needed by conservation managers. Objective: To analyse and describe the anatomy of the visceral skeleton, visceral musculature, digestive tract and its adjoining glands; as well as the diet. Methods: The trophic anatomy was performed on 20 adult specimens of both sexes, through the manual dissection; and stomach contents analysis was performed in 60 individuals to describe the diet. Results: As notable characters of the visceral skeleton of T. hildebrandi we found the posterior notch of the premaxillary, the presence of the “coronoid cartilage”, the tricuspid shape of the gill rakers of the first branchial arch, and the presence of the splenial bone; some outstanding characters of the visceral musculature are the origin of the retractor dorsalis muscle from the first four vertebral centra, and the division of the pharyngoclavicularis externus muscle into two sections (A and B). The notable characters of the digestive tube are the absence of stomach and pyloric caeca, and the presence of the “intestinal valve”. The insects of the Chironomidae family (53% IVIr) were the dominant item in the diet of the Tlaloc hildebrandi. Conclusions: The organization of the digestive system of T. hildebrandi corresponds to the general morphologic pattern of the Cyprinodontiformes; however, we register as new information for fish, the presence of the “coronoid cartilage” and the “intestinal valve”. The structures of the trophic morphology and the components of the diet, confirm us that T. hildebrandi is a carnivorous-insectivorous fish.